An Analysis on Students’ Pronunciation Error in English Diphthong - Umarul Dirgan Ramadhan; Laila Wati; Muhammad Junaidi Marzuki; Usuluddin Usuluddin; Adib Nazri (STIKes Ibnu Sina Ajibarang, 2023)
This research analyzes students’ pronunciation errors in English diphthongs in MA NW Teko. The objective was to identify commonly mispronounced errors. The research is descriptive qualitative. The subjects were twelfth grade students at MA NW Teko. Fifteen students were chosen as representatives for analysis. Data was collected from oral tests, interviews, and observations. The data source was a short story called